Transition learning center for Youth with Special Needs (TLCYN) - Danila, Mark Ryan B. (Manila : National University, 2012)
This research looked into designing a transition learning center to support the youth with special needs (YSN).
Approval sheet -- Acknowledgement -- Abstract -- Table of contents -- List of tables -- List of figures -- Chapter 1. The problem and its setting -- Chapter 2. Research methodology -- Chapter 3. Terms of references -- Chapter 4. Data gathering, collation and analysis of data -- Chapter 5. Design framework -- Chapter 6. Translations -- Chapter 7. Findings, conclusion and recommendation -- Chapter 8. Deliberations & final revisions.
Includes bibliographical references.
Keywords: LEARNING CENTER -- PLANNING